2019
DOI: 10.1007/s40195-019-00959-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of γ′ Particles in Ni-Based Superalloy Weld Joint and Its Effect on Impact Toughness During Long-Term Thermal Exposure

Abstract: Effects of long-term thermal exposure on γ′ particles evolution and impact toughness in the weld joint of Nimonic 263 (N263) superalloy were deeply studied at 750 °C. Results showed that the precipitates in the weld metal were mainly composed of fine γ′ particles, bulky MC carbides, and small M 23 C 6 carbides. With the thermal exposure time increasing from 0 to 3000 h, γ′ particles in the weld metal grew up from 19.7 nm to 90.1 nm at an extremely slow rate. After being exposed for 1000 h, γ′ particles coarsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Moreover, the PWHT process facilitated the precipitation of carbides, which promoted the formation of the micron grade large-size MC rich in Ti and Mo as well as the nano grade size M 23 C 6 rich in Cr as shown in Figure 2(g). These findings were also been proved in our previous research [21]. The microstructure of the WM is significantly different with the BM although they have similar compositions.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the PWHT process facilitated the precipitation of carbides, which promoted the formation of the micron grade large-size MC rich in Ti and Mo as well as the nano grade size M 23 C 6 rich in Cr as shown in Figure 2(g). These findings were also been proved in our previous research [21]. The microstructure of the WM is significantly different with the BM although they have similar compositions.…”
Section: Resultssupporting
confidence: 87%
“…Besides, there are some polygonal precipitates shown in Figure 2(a), which was considered as Ti(C, N) combining with relevant studies [9, 20]. Except that, there are other three kinds of precipitates in the N263 BM: fine γ ′ particles, bulky MC rich in Mo, Ti and granular M 23 C 6 rich in Cr, which had been proved in our previous research [21]. The morphology of carbides in the BM was shown in Figure 2(e).…”
Section: Resultsmentioning
confidence: 62%
“…Arulmuruan et al [22] reported the presence of Mo and W-rich secondary phases in the inter-dendritic region (IDR) of the 686 superalloy weld metal, which was welded by electron beam method, as the main factor reducing the ductility and toughness of the joint. In another study by Fan et al [23] on Nimonic 263 weld metal, it was found that as the heat input to the weld increased, the γ′ particles became larger, resulting in a reduction in impact toughness. In fact, by increasing the heat input to the weld, the ɳ phase, which was formed by the decomposition of MC carbide, reduced the weld toughness by being at the grain boundary and preventing the crack from extension.…”
Section: Introductionmentioning
confidence: 97%
“…Liu et al [23] studied the microstructure and properties of the new wrought nickel-based superalloy under heat exposure at 650 • C, and found that after 2300 h of thermal exposure, there was no TCP phase and no γ ′ region near the grain boundary, and the γ ′ phase remained spherical (the critical size of the γ ′ phase was 40-45 nm), and found that the tensile strength and yield strength of the alloy increased after heat exposure at 650 • C. He et al [24] studied the microstructure of Hastelloy N superalloy-brazed joints after heat exposure, and found that M 5 B 3 particles were introduced into the isothermal solidification zone (ISZ) of the joints after thermal exposure, resulting in a reduction in brazed-joint strength. Fan et al [25] conducted a 750 • C heat-exposure experiment on the TIG-welded joints of the Nimonic 263 (N263) superalloy, and found that with the increase in heat exposure time, the γ ′ phase in the fusion zone and base-metal area became coarser, and some γ ′ phases were transformed into slat-like η phases, and the precipitation of grain boundaries' η slats hindered crack propagation; these changes of the microstructure resulted in a decrease in the impact toughness of the joints. Liu et al [26] investigated the changes in the microstructure and properties of the second-generation single-crystal superalloy DD6 under long-term aging, and showed that when aging at 980 • C for 1000 h, the alloy was absent in the second phase while the µ-phase precipitated while aging for 5000 h and 7500 h. At present, there are few studies on the structure and properties of nickel-based superalloy-welded joints under heat exposure, and it is of great significance to study and characterize the structural changes of welded joints to evaluate the performance of welded joints.…”
Section: Introductionmentioning
confidence: 99%